A opção pelos pobres na poesia de Patativa do Assaré - Tavares, Emerson Sbardelotti (2016)
From the perspective of theology, from the fundamentals of liberation theology insights, we intend to analyze the poetry of Patativa do Assaré poet, the cut in his work suggests and points out the option for the poor, well before it is proclaimed and assumed in Medellin Conference (1968, Columbia) and then resumed without the same prophetic freedom in Puebla Conference (1979, Mexico), Santo Domingo (1992 Dominican Republic) and Aparecida (2007, Brazil), doing so, a link, a bridge between theology and literature. The purpose of the Option for the Poor in Poetry Patativa do Assaré is to show how the option for the poor, biblical heritage, Vatican II heritage, with respect to assumptions and expectations than would be worked out and discussed in the Episcopal Conferences Latin American and Caribbean would be a poetic instrument of liberation in the voice and words of Patativa do Assaré. The main hypothesis is to show that Patativa do Assaré, by divine inspiration, becomes a sacred agent, becomes a representative of the Option for the Poor as it makes her poetry a prophecy where the watchwords are: truth, justice, freedom, brotherhood, equality and land reform. All current, useful and necessary. In Patativa do Assaré, the Option for the Poor that made by his poetry, is the Word of God touching humanity is doing in us, poetry. The option for the poor, assumed by the poet, was evident in all his books and in interviews he gave throughout his life. The results obtained from this research was to find out that there is a vast territory to be explored this relationship between theology and literature, as yet, everything is new and small steps are being taken in this direction. It was concluded that the Option for the Poor is useful, it is necessary, is current and should be lived, assuming all the consequences even martyrdom, as Patativa do Assaré, despite not being the poet a theologian, has always sought to be consistent with their choices; among them he never gave up the truth, justice, freedom and living among the people